INCIDENCE OF FUNGAL FOLIAR BLIGHTS ON DIFFERENT MANGO CULTIVARS IN SOKOTO METROPOLIS - Zainab, M. B; Shinkafi, S.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2017)
A field survey was carried out to investigate the incidence of fungal leaf blights disease of mango (Mangifera indica) in Sokoto metropolis using random sampling methods. Survey was carried out in six mango growing areas; Arkilla, Dambuwa, Gagi, Illela, More and the permanent site of the Usmanu Danfodiyo University, Sokoto areas. A total of 125 healthy and diseased plant leaves were collected by detached technique. The diseased leaves were taken to the laboratory for culture, isolation, and identification of pathogens. Disease incidence was determined using disease index and severity scale of 0-4 rating. Results from isolation revealed Colletotrichum gloesporioides and other pathogenic fungi. The incidence of leaf blight was greater in UDUS area with percentage of occurrence of (56.75%) while it was lower in Arkilla area (31.65%). In relation to the disease incidence in different mango varieties, the incidence was higher with Mai bindiga Mango variety (78%) whereas, improved variety was the least infected (25.8%). Therefore, the statistical analysis conducted showed that at 5 % disease severity from the study was not significant with mango location but it was with Mango variety. Anthracnos caused by C. gloesporioides was severe due to cultural practices in the areas. Enlightening farmers on proper cultural practises aimed at boosting mango yield and reducing pathogen invasion is recommended.